PENGARUH STATUS EKONOMI , PENGETAHUAN TENTANG SMKDAN PEMOTIVASIAN ORANG TUA TERHADAP MINAT MELANJUTKAN KE SMK PADA SISWA KELAS IX SMP NEGERI DI KECAMATAN WONOSOBO TAHUN 2014 (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This study aims to determine the review of the effect of economic status, knowledge of vocational schools, and motivating parents to intention to continue to secondary school vocational secondary school students in the District of Wonosobo State.This research is a quantitative study that explains the phenomenon of research based on the facts that measured quantitative data . Data were drawn from the population of all class IX students at Junior High School in the District of Wonosobo. Number of Junior High School in the District of Wonosobo three (3 ) schools. Samples taken amounted to 243 people with a proportional random purposive sampling technique. Instrument research using questionnaires. Methods of data analysis used of linear regression equation. Testing requirements analysis used normality test, linearity, and multicollinearity test with a significance level of 95%.Based on the results of this study concluded that: (1) There was the influence of economic status, knowledge and motivating parents to interest of Junior High School students to continue in vocational schools in the District of Wonosobo. (2) There was a negative and significant effect of the economic status of parents to interest of Junior High School students to continue in vocational schools in the District of Wonosobo. Economic status of parents of low cultivate students' interest to continue higher vocational education. (3) There was a positive and significant effect of the knowledge of parents to interest of Junior High School students to continue in vocational schools in the District of Wonosobo. Knowledge of vocasional parents can better be a source of information for the child so that it has a higher interest to continue in vocational schools. (4) There was a positive and significant effect of motivating parents to interest of Junior High School students to continue in vocational schools in the District of Wonosobo. Motivation is provided by parents can increase the interest of students to attend school in vocasional. Interest in junior high school students to continue their education in vocational should be based on the good judgment that is consistent with the purpose of vocational education. Economic community groups as well as middle and high school committees should be given the socialization of vocational education goals better.